2019
DOI: 10.1016/j.biopsych.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Joint Attention in Infancy and the Emergence of Autism

Abstract: BACKGROUND: In typical infant development, parents and their children jointly contribute to establishing frequent episodes of joint attention that boost language acquisition and shape social cognition. Here we used novel live eyetracking technology to evaluate the degree to which autism spectrum disorder (ASD) is related to reduced responding to others' joint attention bids in infancy (RJA) and to a reduced tendency to initiate joint attention episodes (IJA). Because young infants use their gaze for both RJA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 41 publications
7
93
2
1
Order By: Relevance
“…Interestingly, these individual differences in social visual attention to faces are not related to autism severity, autism symptoms, or social behavior among the adolescents with ASD. These findings converge with those from infant [20], toddler [29], and child [21] studies reporting no differences in visual attention to faces at the group level. We also found that fixation durations to target objects were comparable in the ASD and TD groups (as was the variance among these durations) in the Gaze Following Task.…”
Section: Following Eye Gaze For Referential Understandingsupporting
confidence: 86%
“…Interestingly, these individual differences in social visual attention to faces are not related to autism severity, autism symptoms, or social behavior among the adolescents with ASD. These findings converge with those from infant [20], toddler [29], and child [21] studies reporting no differences in visual attention to faces at the group level. We also found that fixation durations to target objects were comparable in the ASD and TD groups (as was the variance among these durations) in the Gaze Following Task.…”
Section: Following Eye Gaze For Referential Understandingsupporting
confidence: 86%
“…Few studies have measured gaze following in live interaction in infants with later ASD using eye-tracking. As in our study, Nyström et al (2019), found no outcome difference in the amount of first looks directed to referent vs. distractor in 10-month olds infants at risk for ASD. In contrast, Presmanes et al (2007) and Sullivan et al (2007) showed that HR-ASD infants directed fewer first looks to referents but they did not employ eye tracking which means we do not know where infants look when they did not correctly follow gaze, i.e., did they make an incorrect first look to another object or did they not disengage from the face?…”
Section: Discussionsupporting
confidence: 62%
“…However, repeated attention to sources of sensory uncertainty (e.g., others' saccades), combined with an inability to adequately leverage predictions to explain away this uncertainty (owing to too much sensory precision), means that such individuals may develop idiosyncratic or atypical phenotypic expressions of the adaptive prior for alignment (e.g., avoiding eye gaze; Tanaka and Sung, 2016). In other words, early atypicalities in the internal dynamics generating evidence gathering cycles of action-perception may have downstream effects on joint attentional skills (Charman et al, 1997;Nyström et al, 2019), attunement to and use of communicative action policies (Loveland and Landry, 1986;Warlaumont et al, 2014), mental state inference (Tager-Flusberg, 2007), and other means for alignment (Heasman and Gillespie, 2019). In short, aberrant inference in a prosocial, developmental setting may easily lead to a pernicious kind of dyslexia -not for the written word -but for any communicative exchange (i.e., joint inference).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%